The heterogeneity of the functional, metabolic, and molecular responses of skeletal muscle and clinical adaptations to exercise training in pre-clinical and human models - Farrash, Wesam (2020)
Introduction: Exercise training triggers numerous physiological adaptations that promote individual general health, which were found to be mediated through myokines. Exercise training stimulates myokines expression from skeletal muscle and released into the circulation. However, individuals respond very differently to exercise training i.e. high responders to low/non-responders. The aims of the thesis were i) to explore the impact of Fndc5/irisin (a myokine) on skeletal muscle metabolism and fat remodelling, ii) to investigate how trainability, acute and chronic exercise effect the release of myokines, and lastly, iii) to test the existence of low/non-responder to all exercise training modes and the impact on health benefits. Methods: Fndc5 was locally overexpressed in rat hind-limb via in vivo electroporation technique. Molecular analysis were performed in control and overexpressed muscle and also adipose tissue. Inbred animal model, low responder (LRT) and high responder (HRT) trainers, was used to investigate trainability on myokines’ profiles, which were examined at baseline, following acute exercise, and after 3-weeks of training. Finally a novel human clinical intervention study was conducted wherein participants were studied following, 4-weeks of either endurance or resistance training, then crossed over following a 6-week washout. Findings: Fndc5 overexpression resulted in physiological levels of circulating irisin, which had minimal impact on skeletal metabolism and browning adipose tissue. Exercise training caused an acute elevation of myokines, while 3-weeks training increased/decreased myokines baseline concentrations and temporal responses area under the curve. In general, ‘myokine’ profiles were not able to clearly distinguish between LRT/HRT animals and explain their trainability. In the human cross-over study, the 6-weeks of detraining were enough to washout the enhanced mode specific adaptions. The adaptive responses varied from high to low/non responder with suggested mode preference for individual. Finally, the magnitude of fitness adaptive responses to training modes were not link to the extent of health benefits responses.